Childhood socioeconomic background and elevated mortality among the young adult second generation in Sweden: a population-based cohort study - Lisa Harber-Aschan; Matthew Wallace; Ben Wilson; Eleonora Mussino; Siddartha Aradhya (BMJ Publishing Group, 2024)
Introduction The native-born children of migrants represent one of the fastest-growing and most diverse young populations in the world today. A growing body of research highlights an elevated young adult mortality risk in this 'second generation' (G2) relative to the majority population at the same ages. Previous studies have tried to understand this increased risk by examining its association with inequality in the adult socioeconomic background (SEB) of the G2. Here, we instead analyse the association of second-generation status with childhood SEB.Methods We use administrative register data from Sweden to fit multistate, competing-risk, flexible parametric survival models on a data set of 13 404 deaths in 2.35 million young adults. We examine mortality from all causes and specific causes of death at the generational level and by parental region of birth, both before and after having adjusted for childhood SEB.Results The G2 have higher all-cause mortality hazard rates (HR=1.29 (95% CIs=1.23 to 1.34)) than the majority population before adjusting for childhood SEB. Following adjustment, the size of the hazard rate is smaller, but remains higher than the majority population (aHR=1.16 (95% CIs=1.11 to 1.21)). The G2 additionally experience persistent and higher hazard rates of mortality from suicide (aHR=1.29 (95% CIs=1.20 to 1.39)), substance misuse (aHR=1.41 (95% CIs=1.26 to 1.58)) and assault (aHR=2.54 (95% CIs=2.02 to 3.20)). By parental origins, similar patterns to those described are documented among G2 that have at least one parent born in Finland, the other Nordic countries, former Yugoslavia, the rest of Europe, sub-Saharan Africa, Northern Africa, and Iran and Iraq. However, higher all-cause (aHR=1.42 (95% CIs=1.33 to 1.51)) and external-cause hazard rates of mortality (aHR=1.59 (95% CIs=1.48 to 1.72)) only persist among G2 with parent(s) born in Finland.Conclusions G2 with various parental origins have higher mortality rates than the majority population do, and this difference is partly explained by their childhood SEB.